2011
DOI: 10.1167/iovs.11-7686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shear Stress on the Gene Expressions of Endothelial Nitric Oxide Synthase, Endothelin-1, and Thrombomodulin in Human Retinal Microvascular Endothelial Cells

Abstract: Long-term exposure to a physiological shear stress in the retinal arterioles up-regulated eNOS and TM mRNA expressions and downregulated ET-1 mRNA expression in HRMECs. These results suggest that shear stress may be associated with the vasoregulatory and antithrombotic properties of retinal vessels under physiological conditions present during retinal circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 41 publications
7
50
1
1
Order By: Relevance
“…22 In an endothelial cell culture experiment, Ishibazawa et al showed that decreased shear rate is able to modulate endothelial gene expression including decreased thrombomodulin and decreased endothelial nitric oxide along with increased endothelin-1, with an overall effect of vasoconstriction and prothrombogenic endothelial profile. 33 Overall, the low shear rate seen in our patients compared to controls is consistent with highly abnormal endothelial function in these poorly controlled diabetics, which would severely compromise their response to laser therapy as well as their overall clinical outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…22 In an endothelial cell culture experiment, Ishibazawa et al showed that decreased shear rate is able to modulate endothelial gene expression including decreased thrombomodulin and decreased endothelial nitric oxide along with increased endothelin-1, with an overall effect of vasoconstriction and prothrombogenic endothelial profile. 33 Overall, the low shear rate seen in our patients compared to controls is consistent with highly abnormal endothelial function in these poorly controlled diabetics, which would severely compromise their response to laser therapy as well as their overall clinical outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…21 The laminar flow is associated with shear stress, which is important for regulating blood flow. 22,23 The DOCT flowmeter can visualize the retinal blood velocity profile (RBVP), which is the velocity profile of the red blood cells in the horizontal center of a vessel at a given moment (Fig. 1C).…”
Section: Discussionmentioning
confidence: 99%
“…In retinal endothelial cells, continuous laminar shear stress upregulates the expression of TM in a time-and dose-dependent manner [49]. Some studies have nonconsistently shown decreased endothelial TM expression upon cyclic strain [8].…”
Section: Tm In Mhtmentioning
confidence: 99%